KEPUASAN MASYARAKAT PADA PELAYANAN DONOR DARAH DI PALANG MERAH INDONESIA (PMI) CABANG PONTIANAK - Syamsi Hidayat; Helman Fachri; Samsuddin Samsuddin (Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the community satisfaction with blood donor services at the Indonesian Red Cross (PMI) Pontianak Branch. This study uses a survey method, which is a research technique in which information is collected through questionnaires. The population is people who are still actively donating blood at the Pontianak branch of PMI. While the sample used in this study is based on incidental sampling technique, a sample of 100 people will be used as samples.Analysis of the data used in this study is a Cartesian diagram. Analysis is used using the SPSS 16.0 for Windows program to make it easier to process and interpret the results of the study. The results of this study indicate that: Most respondents are male, aged 20-25 years, have a high school education, work as private employees, earn Rp. 2,000,000.00 - Rp. 2,999,999.00 and the majority of blood donors 2 times a year and satisfaction scores (X = 4.05) equal to the value of interest ((= 4.05), meaning community satisfaction with blood donor services at the Indonesian Red Cross (PMI) Pontianak Branch is satisfied.